Aerobic biological wastewater treatment by fluidized bed (theoretical approach) - Fernando, Sampathawaduge Wimal Hemraj Sethsiri; Nguyen, Cong Thanh; Vigneswaran, S.; Ugnaki, S.; The Royal Netherlands Government (Bangkok : Asian Institute of Technology, 1985)
The mathematical models on biological Fluidized Beds which have been developed in the past for the removal of organic matter have conSidered only one type 01 microorganisms, either the attached microorganisms or the suspended microorganisms. It is to be noted that the removal Kinetics tor the attached microorganisms and the suSpended microorganisms are different Irom each other. In the present study, the mathematical model has been developed to describe the removal mechanism or the Tapered Fluidized Bed reactor. This model considers the activity or both the suspended microorganisms and the attached microorganisms tor the removal of the organic matter. In another respect, unlike the previous models that have been developed, the present model is Singular in that it CODSldeIS a tapered reactor. A tapered reactor has a relative adVantage at preventing the outward oi biomass particles. Since both types of microorganisms tor, the removal of organic hatter has been considered, accordingly, the appropriate kinetics have been used for each type of microorganism. For the suspended microorganisms Monod Kinetics Here applied and tor the attached microorganisms the use of Biofilm Kinetics were used.
Thesis (M. Eng.) - Asian Institute of Technology, 1985
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering
Keywords: Sewage -- Purification -- Biological treatment